Thermal Stability and Kinetic Study of Fluvoxamine Stability in Binary Samples with Lactose - Faranak Ghaderi; Mahboob Nemati; Mohammad Reza Siahi-Shadbad; Hadi Valizadeh; Farnaz Monajjemzadeh (Tabriz University of Medical Sciences, 2017)
Purpose: In the present study the incompatibility of FLM (fluvoxamine) with lactose in solid state mixtures was investigated. The compatibility was evaluated using different physicochemical methods such as differential scanning calorimetry (DSC), Fourier-transform infrared (FTIR) spectroscopy and mass spectrometry. Methods: Non-Isothermally stressed physical mixtures were used to calculate the solid-state kinetic parameters. Different thermal models such as Friedman, Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunose (KAS) were used for the characterization of the drug-excipient interaction. Results: Overall, the incompatibility of FLM with lactose as a reducing carbohydrate was successfully evaluated and the activation energy of this interaction was calculated. Conclusion: In this research the lactose and FLM Maillard interaction was proved using physicochemical techniques including DSC and FTIR. It was shown that DSC- based kinetic analysis provides fast and versatile kinetic comparison of Arrhenius activation energies for different pharmaceutical samples.